2016
DOI: 10.1088/0741-3335/58/6/065005
|View full text |Cite
|
Sign up to set email alerts
|

High frequency magnetic fluctuations correlated with the inter-ELM pedestal evolution in ASDEX Upgrade

Abstract: In order to understand the mechanisms that determine the structure of the high confinement mode (H-mode) pedestal, the evolution of the plasma edge electron density and temperature profiles between edge localised modes (ELMs) is investigated. The onset of radial magnetic fluctuations with frequencies above 200 kHz is found to correlate with the stagnation of the electron temperature pedestal gradient. During the presence of these magnetic fluctuations the gradients of the edge electron density and temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
65
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 46 publications
11
65
0
Order By: Relevance
“…As already mentioned the second branch starts with n = −7, −8 already in phase II whereas the other branches show up in this phase first. As it was shown by Laggner et al [14] the here discussed inter-ELM modes are placed in the strong pressure gradient region close to the plasma boundary. Some of the following assumptions used for the localization are only valid in this edge region.…”
Section: Phase IIIsupporting
confidence: 72%
“…As already mentioned the second branch starts with n = −7, −8 already in phase II whereas the other branches show up in this phase first. As it was shown by Laggner et al [14] the here discussed inter-ELM modes are placed in the strong pressure gradient region close to the plasma boundary. Some of the following assumptions used for the localization are only valid in this edge region.…”
Section: Phase IIIsupporting
confidence: 72%
“…This requires detailed investigations in the future. For example, in H-mode quasi-coherent modes with low frequency broadening are observed [52], while in I-mode a weakly coherent mode with high frequency broadening is observed [53,54]. In general, it is recommended to verify phase velocity measurements based on a frequency-dependent technique with a wavenumber-dependent technique, and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…The EPED model predicts that, when a critical pressure gradient for kinetic ballooning modes is reached, these modes lead to a clamping of the pressure gradient. A correlation of this clamping with high‐frequency modes has been confirmed experimentally, although Laggner et al could not confirm the ballooning character of the observed modes. Typically, while the maximum pressure gradient remains clamped, the pedestal grows further inwards until a large ELM crash appears.…”
Section: Type‐i Elmsmentioning
confidence: 94%